OPTIMASI PENGGUNAAN TENAGA KERJA KELUARGA PETANI TERNAK SAPI DI SEKITAR HUTAN ADAT KABUPATEN KAMPAR - Latifa Siswati; Rina Novia Yanti (Jurnal Peternakan, 2008)
Labour optim.a1ization reached by selecting the suitable subfarming system with labour capability and teamwork system. The objective of the study was to know the allocation of family labour to maximize the income of <:attle farming family who live around adat forest The study was conducted in adapt forest Rumbio in Kampar. The data collected in two stages sampling technique. First, to get three villages from nine one, was used purposive random sampling and simple random sampling. Then, the responden was choiced with criteria have cattle and plantation. The data analyzed using linear programming. The result indicated that the allocation of family labour higher in plantation than cattle farming. Through optimalization the family labour, the family income will beincrease.